Entrepreneurship Everywhere: Across Campus, Across Communities, and Across Borders. (19th December 2017) - Hornsby, Jeffrey S.; Messersmith, Jake; Rutherford, Matthew; Simmons, Sharon
Abstract : This paper introduces the theme of this special issue related to Entrepreneurship Everywhere: Across Campus, Across Communities, and Across Borders. We explore three critical points as we set up the accepted articles for the special issue. First, if we are everywhere are we anywhere? Second, we focus on the importance of collaboration. Third, we discuss the importance of strategically planning on how your efforts intervene or integrate into the wider ecosystem.